2021
DOI: 10.3390/su13169290
|View full text |Cite
|
Sign up to set email alerts
|

Freezing and Heating Tolerance of Pinus nigra Seedlings from Three South to North Balkan Provenances

Abstract: To meet the restoration and reforestation goals in the changing environment, the translocation of genotypes and species northward and upward need to be considered to a great extent. Pinus nigra is a genetically diverse, drought sensitive species, with cold hardiness comparable to other tree species under the same climatic conditions. This study tested frost hardiness (whole plant freezing test—WPFT, and electric conductivity—EC test), and heat tolerance (heat tolerance test) of P. nigra seedlings from two sout… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 37 publications
(40 reference statements)
0
2
0
Order By: Relevance
“…Several studies have demonstrated that using sulfuric acid was more effective than other treatments for different forest species [47,57,65]. To break the seed dormancy, the tegument must be deteriorated; in natural conditions, this 'damage' occurs as a result of the action of many elements on the seed tegument, such as low temperatures (frosts), high temperatures (fires), and so on [45,46]. The scarification of the silver fir seeds failed to produce a high percentage of germination in our experimental conditions, but, in contrast, Atonik, a biostimulator used to stimulate both seed germination and seedling rooting [50], significantly improved the germination for all the silver fir provenances.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several studies have demonstrated that using sulfuric acid was more effective than other treatments for different forest species [47,57,65]. To break the seed dormancy, the tegument must be deteriorated; in natural conditions, this 'damage' occurs as a result of the action of many elements on the seed tegument, such as low temperatures (frosts), high temperatures (fires), and so on [45,46]. The scarification of the silver fir seeds failed to produce a high percentage of germination in our experimental conditions, but, in contrast, Atonik, a biostimulator used to stimulate both seed germination and seedling rooting [50], significantly improved the germination for all the silver fir provenances.…”
Section: Discussionmentioning
confidence: 99%
“…To break seed dormancy, different physical or chemical stimuli act on the seeds, or the seed integument must be damaged; in natural conditions, this damage occurs due to the action of different factors, such as low temperatures (frosts), high temperatures (fires) [45,46]. Currently, different methods are used to scarify the seeds, the mechanical scarification method being one of the most used [47][48][49].…”
Section: Introductionmentioning
confidence: 99%